Regularities of structure formation and physical properties of multilayered composites based on W, Ta, Нf, Ti, Mo, Сr, Al, and С - Perekrestov , V. I.; Kosminska , Yu. O.; Gannych, Yu. V.; Kornyushchenko , G. S. (Physics and Chemistry of Solid State, 2020)
New fabrication technique of multilayered composite coatings on inner surface of pipes is developed which is based on ion–plasma sputtering of rod–like target composed of various metals and graphite. It is established that gradient change of elemental composition in the direction Сr→W→Mo→Ta→Hf→Ti→C→Ti/Al→C is accompanied by transition from metal mixture carbide to titanium carbide with the grain sizes of 8–15 nm. It is found that increase in microhardness up to 26 GPa is caused by additional surface heating by thermal radiation from the ion–heated rod and by elemental composition of the composite layers.